Satisfaction and Complaints of Patients with Removable Partial Dentures: In Sample at Baghdad City, Iraq (Medico Legal Update, 2021)
Objective: This study examined patients’ complain regarding pain on eating, esthetic and speech problemsand gag reflex with various types of removable partial dentures (RPDs).Method: The study sample included 60 RPD wearers (36 females and 24 males) aged between (25-60)years old. Sex, age, occupation, any experience with previous RPDs, and the complaint with RPDs wererecorded. Data were analyzed using Chi-square test was applied for comparison among different variablesof oral complaints related to removable prosthesis; an independent a sample t-test was utilized. A P-value